PERSEPSI LABA PEDAGANG KELONTONG PASAR RAKYAT BANYUASRI - Putu Eka Wati; Ni Wayan Yulianita Dewi; Putu Ria Astria (Jurnal Widya Akuntansi dan Keuangan, 2023)
Abstract : The purpose of this study is to describe the meaning of profit according to grocery traders in the Banyuasri People's Market, Buleleng Regency. The selection of grocery traders in the Banyuasri People's Market in this study was based on the close relationship between the profession of grocery traders, with money and society. The profession of a grocer, money and society is an endless circle. All three are interrelated and related in various circles of life. There is a tool that brings the two parties together, namely "Money". It keeps rolling and doesn't stop. Exploring profit-related information is important to do before implementing standards, given the minimal knowledge possessed by traders in Banyuasri Market regarding financial reports, due to different understandings of profit, even though profit is the central point of business activity. The paradigm in this study uses an interpretive paradigm. The data analysis method uses the philosophy of hermeneutic intentionalism. Intentional hermeneutics is used in this study, because the researcher seeks to interpret and explore the meaning in the text or spoken language of the informants and the thoughts of the informants. The result of this study is that the informants perceive profit as material gain, spiritual gain and spiritual satisfaction benefit.